ChemInform Abstract: Conversion of 2‐Furylcarbinols with Alkyl or Aryl Azides to Highly Functionalized 1, 2, 3‐Triazoles via Cascade Formal [3 + 2] Cycloaddition/Ring‐Opening. Issue 13 (March 2015) - Guo, Jiawei; Yu, Binxun; Wang, Ya‐Nan; Duan, Dongyu; Ren, Li‐Li; Gao, Ziwei; Gou, Jing
Abstract The title reaction has a wide substrate scope and proceeds with high (E)‐stereospecificity.